Changes in vertical jump height and sprint time during a congested match schedule in youth female soccer players - Spalding, J.; Dotterweich, A. R.; Gentles, J.; Eveland-Sayers, B.; Sayers, A. L. (The Sport Journal, 2021)
Purpose: The purpose of this study was to examine changes in jump height and sprint time and to assess the relationship between relative changes in jump height and accumulated training load during a congested match schedule in youth female soccer players. Methods: This study included data from 14 youth female soccer players who performed countermovement jump testing pre- and post-match, post-tournament, as well as sprint testing pre- and post-tournament. A one-way repeated measures ANOVA was conducted to compare changes in jump height over the course of the tournament. A paired sample t-test was performed to compare sprint time between pre- and post-tournament, and Pearson product moment correlations were used to determine the relationship between percent change in jump height and accumulated training load. Results: Jump height decreased significantly (p < 0.001) between time periods during the tournament, and sprint time increased significantly (p = 0.001). There was no significant relationship between percent change in jump height and accumulated training load. Conclusion: This study found that jump height decreased over the course of the tournament and there was a significant increase in sprint time from pre- to post-tournament. Applications in Sport: These results suggest that appropriate recovery strategies and training are needed to assist players in coping with the demands of a congested youth soccer schedule.